Tumor‐induced myeloid‐derived suppressor cell subsets exert either inhibitory or stimulatory effects on distinct CD8+ T‐cell activation events. Issue 11 (25th August 2013) - Schouppe, Elio; Mommer, Camille; Movahedi, Kiavash; Laoui, Damya; Morias, Yannick; Gysemans, Conny; Luyckx, Ariane; De Baetselier, Patrick; Van Ginderachter, Jo A.
<x xml:space="preserve">Abstract</x> Tumor growth coincides with an accumulation of myeloid‐derived suppressor cells (MDSCs), which exert immune suppression and which consist of two main subpopulations, known as monocytic (MO) CD11b+CD115+Ly6G−Ly6Chigh MDSCs and granulocytic CD11b+CD115−Ly6G+Ly6Cint polymorphonuclear (PMN)‐MDSCs. However, whether these distinct MDSC subsets hamper all aspects of early CD8+ T‐cell activation — including cytokine production, surface marker expression, survival, and cytotoxicity — is currently unclear. Here, employing an in vitro coculture system, we demonstrate that splenic MDSC subsets suppress antigen‐driven CD8+ T‐cell proliferation, but differ in their dependency on IFN‐γ, STAT‐1, IRF‐1, and NO to do so. Moreover, MO‐MDSC and PMN‐MDSCs diminish IL‐2 levels, but only MO‐MDSCs affect IL‐2Rα (CD25) expression and STAT‐5 signaling. Unexpectedly, however, both MDSC populations stimulate IFN‐γ production by CD8+ T cells on a per cell basis, illustrating that some T‐cell activation characteristics are actually stimulated by MDSCs. Conversely, MO‐MDSCs counteract the activation‐induced change in CD44, CD62L, CD162, and granzyme B expression, while promoting CD69 and Fas upregulation. Together, these effects result in an altered CD8+ T‐cell adhesiveness to the extracellular matrix and selectins, sensitivity to FasL‐mediated apoptosis, and cytotoxicity. Hence, MDSCs intricately influence different CD8+ T‐cell activation events in vitro, whereby some parameters are suppressed while others are stimulated.